FINITE ELEMENT MODELLING OF WEAR PROCESS OF A PEEK-STEEL SLIDING PAIR AT ELEVATED TEMPERATURE - Kónya, László; Váradi, Károly; Friedrich, Klaus (Periodica Polytechnica Mechanical Engineering, 2005)
The operational conditions for polymer-steel sliding pairs frequentlyproduce higher temperature because of the frictional heat generation and/orsome environmental sources. To study the wear behaviour an incremental wearsimulation technique have been developed, which can consider the temperature-and time-dependent behaviour of polymer materials and evaluate the contactbehaviour during the wear process by changing the initial clearance betweenthe pin and disc according to the linear wear equation. The wear simulationtechnique proposed is applied for a Pin-on-Disk configuration consideringcreep behaviour of a PEEK material, the frictional heat generation and thethermal expansion. The results illustrate the initial part of the wearprocess, which involves the edge-like contact and the full contact phases.